Uncharted water conflicts ahead: mapping the scenario space for Germany in the year 2050 - Kosow, Hannah; Brauner, Simon; Brumme, Anja; Hauser, Wolfgang; Hölzlberger, Fabian; Moschner, Janina; Rübbelke, Dirk; Vögele, Stefan; Weimer-Jehle, Wolfgang (Frontiers in Water, 2024)
IntroductionIn recent years, conflicts surrounding the use, distribution, and governance of surface water and groundwater in Germany have gained prominence in the media, on the political agenda, and in research. Increasing effects of climate change, such as heatwaves and drought but also extreme rain events and flooding, are considered to become more prominent and pressing in the future by different societal actors. However, it remains highly uncertain if and what type of conflicts related to water quantity Germany might actually face in the future (and how they will be framed). This paper addresses one dimension of this uncertainty—namely the future context uncertainty of possible resource and water governance conflicts. Our research contributes to an improved understanding of the uncertainty concerning future climatic, natural, land use related, political, economic, and other societal contexts that could impact water conflicts.MethodWe ask: What are possible coherent context scenarios for Germany in the year 2050, and how are they expected to influence future water conflicts? In an expert-based process, we apply a qualitative and systematic method of systems analysis, cross-impact balances (CIB). With CIB, we build internally consistent scenarios of possible futures and map the future scenario space.Results and discussionDiversity mapping with a new CIB web application of the ScenarioWizard reveals that the scenario space is rather large and diverse. The identified scenario space of n = 355 internally consistent scenarios spans four most diverse scenarios “Polycrisis,” “Economy and agriculture in crisis,” “Growth through adaptation to climate change,” and “Sustainable transformation.” Depending on the development of future contexts, the risk for future water resource and governance conflicts may unfold in various ways. We conclude that our scenario analysis provides a useful base for research and practice to address the context uncertainty of water conflicts in Germany. Our results can be used for risk assessment, to define societal framework assumptions for societal-hydrological modeling, and to develop robust and adaptive strategies and policies.